Application of ateb-functions to the construction of solutions of some nonlinear partial differential equations - Sokil, B. I. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We construct asymptotic approximations of one-frequency solutions of some nonlinear partial differential equations by using periodic Ateb-functions.